New Sources for Philippe Desportes in the Series of Rime di diversi (1545-1560) - Aceituno Martínez, Eduardo (Thélème. Revista Complutense de Estudios Franceses, 2026)
For several decades, Philippe Desportes’ list of Italian sources has been considered more or less complete. However, we have spotted, in the famous series of Rime di diversi, some undiscovered sources of Desportes, which confirm his incomparable knowledge of the Italian poetry of his time. In this article we will only discuss cases where the relationship between the poems seems indisputable. Among these ten pieces, almost all sonnets, half appear in the Sesto libro delle rime di diversi eccellenti autori (1553); the others are in the Libro primo (1546), Libro quarto (1551), Libro quinto (1552) and Libro settimo (1556). All their authors are relatively little known, and very varied: the only one from whom Desportes takes two poems is Giacomo Mauro. We will briefly comment on each of these discoveries, to try to understand what Desportes owes to the Italian original and what aspects of the model he believes necessary to modify.